Highly Flexible and Efficient All‐Polymer Solar Cells with High‐Viscosity Processing Polymer Additive toward Potential of Stretchable Devices. (4th September 2018) - Chen, Shanshan; Jung, Sungwoo; Cho, Hye Jin; Kim, Na‐Hyang; Jung, Seungon; Xu, Jianqiu; Oh, Jiyeon; Cho, Yongjoon; Kim, Hyeongwon; Lee, Byongkyu; An, Yujin; Zhang, Chunfeng; et al.
Abstract: Considering the potential applications of all‐polymer solar cells (all‐PSCs) as wearable power generators, there is an urgent need to develop photoactive layers that possess intrinsic mechanical endurance, while maintaining a high power‐conversion efficiency (PCE).Herein a strategy is demonstrated to simultaneously control the intercalation behavior and nanocrystallite size in the polymer–polymer blend by using a newly developed, high‐viscosity polymeric additive, poly(dimethylsiloxane‐ co ‐methyl phenethylsiloxane) (PDPS), into the TQ‐F:N2200 all‐PSC matrix. A mechanically robust 10wt% PDPS blend film with a great toughness was obtained. Our results provide a feasible route for producing high‐performance ductile all‐PSCs, which can potentially be used to realize stretchable all‐PSCs as a linchpin of next‐generation electronics. Abstract : Eine mechanisch robuste photoaktive Schicht aus 10PDPS ergibt einen hohen Wirkungsgrad von 6.87 % in herkömmlichen Polymersolarzellen und einen Wirkungsgrad von 5.60 % in elastischen Einheiten mit Graphen‐Elektrode. Diese Zellen behalten über 100 Zyklen mit 3 mm Biegeradius 90 % ihres Wirkungsgrads bei.